Configurational aspects of the concept Berufswahl - Tsisar, Andrii; Zubach, Oksana (My University, 2023)
The concept BERUFSWAHL is a product of the interaction of cognitive and linguocultural categories of the linguistic and cultural worldview. Theprinciples of concept formation are the result of the coordination of mechanisms forreflecting the mental processes of understanding and perceiving the worldview andbackground knowledge. The structure of the conceptBERUFSWAHL is formed dueto associative relations and stereotyping of images and consists of the semanticnucleus and interpretative fields that encode the experience of linguistic personality.The mechanisms of concept formation are fixed on the conceptual(availability of background information about the experience of linguoculture:Berufsalltag, Berufsauffassung, Berufsausbildung), structural (preservation of themechanisms of objectification of the concept:Vo l l-, Zivil-, Traum-, Modeberuf) and evaluative (connotative features of elements of the worldview:Notwendigkeit, Karriere, Life-Wo r k-Balance) levels. National associations serve as the backgroundfor the formation of the value components which provoke unique denotative,significant and connotative features of the cognitive product to increase the volume of the peripheral zones of the concept. The configuration property of the conceptBERUFSWAHL is represented through direct (in verschiedene Berufsbereichereinschnuppern, hinter die Kulissen schauen, Erfahrungen sammeln) and indirect(Tätigkeit, Profession, Maloche) nominations and the elements which reveal thehistoric, social and cultural experience of the formation of ethnic culture explicatinggender, physical, intellectual and spiritual features of the linguistic personality.
Keywords: concept; nomination; integral/differential feature; ethnic oculture; linguistic personality